Migration and Urban Culture in East Germany. Representing Localities in Birgit Weyhe’s Graphic Novel Madgermanes. - Muranyi, Kata (Street Art & Urban Creativity, 2024)
The representation of the aesthetic and political dimensions of the city in the case of comics as a medium touches on a range of issues, from the relationship between comics and street art as well as the representation of urban space and popular culture as identity-shaping factors. Birgit Weyhe’s graphic novel Madgermanes (2016) shows us a specific historical context: after the construction of the Berlin Wall in 1961, a labor force was also needed in East Berlin, as a result of which the leadership invited cheap manpower from communist-oriented countries such as Vietnam, Cuba, Angola, or Mozambique. A total of around 15,000 guest worker immigrants arrived from the latter country in East Berlin within a decade. Three of them are the protagonists of the examined graphic novel, where their stories of integration difficulties, coping practices about finding a home, and rootlessness are told. In the case of the process of acculturation narrated in the medium of comics, the visual representation focuses on the contrast between cultures and the crisis of identity. In this particular graphic novel, this cultural shock is present through the popular and urban culture of the 1970s and 1980s. In this paper, we examine how this graphic novel intersects representations of locality, everyday life, and urban space with the perceptions and experiences of interculturality and media culture.